The Window and the Door - Llewellyn Seibold (Oz, 1989)
Fourth Year Architecture Studio: text by Llewellyn Seibold; works by Jeff Buck, Craig Milde, and Doug Heller. Windows and doors are full of the most poignant and rich expressions we live with. They have a way of persisting in meanings beyond the particular circumstances of fashion or place. Literature, art, and architecture contain references to the sense of meaning engendered by the kind of passage which a door or window creates...